A middle paleolithic and neolithic/chalcolithic flint extraction and reduction complex at Mt. Achbara, Eastern Galilee, Israel. (December 2018) - Finkel, Meir; Gopher, Avi; Ben-Yosef, Erez; Barkai, Ran
Abstract: This paper reports on a recently discovered Middle Paleolithic and Neolithic/Chalcolithic open-air flint extraction and reduction complex at Mt. Achbara in Israel's Eastern Galilee. Lithic assemblages recovered from a few of the hundreds of tailing piles documented in a field survey indicate a combination of Middle Paleolithic finds including Levallois cores and Neolithic/Chalcolithic finds, mainly bifacial (axe/adze) tools. At present, the extraction and reduction complex at Achbara is one of four found on the flint-bearing Eocene Timrat formation of the Galilee. Together, they provide evidence of intensive Paleolithic and Neolithic/Chalcolithic flint extraction, in quantities that most probably exceeded local consumption. After describing the new complex, we discuss its possible relation to nearby occupation sites, with a focus on the Middle Paleolithic Amud Cave. Highlights: Report of a new prehistoric flint extraction and reduction complex at Mt. Achbara, Galilee, Israel Finds attested for Middle Paleolithic, Neolithic/Chalcolithic exploitation Relationship to the nearby Neanderthal Amud Cave suggested